2012
DOI: 10.1021/jf3010405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Antibiofilm, and Mechanism of Action of Novel PEG-Stabilized Lipid Nanoparticles Loaded with Terpinen-4-ol

Abstract: Terpinen-4-ol, an active component of tea tree oil, exhibits broad-spectrum antimicrobial activity. However, the high volatilization of terpinen-4-ol and its nonwettability property have limited its application. Our objective was to synthesize novel nanocarriers to deliver and protect terpinen-4-ol. The polyethylene glycol (PEG)-stabilized lipid nanoparticles were prepared and characterized by scanning electron microscope, Zetasizer, and differential scanning calorimetry. These nanoparticles had an average dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 33 publications
0
26
0
3
Order By: Relevance
“…Recently, Sun et al [99] reported the antibiofilm activity of terpinen-4-ol-loaded lipid nanoparticles against C. albicans biofilms. The compound used (10  μ g/mL) eradicated formed biofilms [99].…”
Section: Antibiofilm Strategiesmentioning
confidence: 99%
“…Recently, Sun et al [99] reported the antibiofilm activity of terpinen-4-ol-loaded lipid nanoparticles against C. albicans biofilms. The compound used (10  μ g/mL) eradicated formed biofilms [99].…”
Section: Antibiofilm Strategiesmentioning
confidence: 99%
“…e compound used (10 g/mL) eradicated formed bio�lms [99]. Finally, the antibio�lm activity of povidone-iodine (PVP-I) was con�rmed by Hosaka et al [100] against Porphyromonas gingivalis and Fusobacterium nucleatum bio�lms.…”
Section: �Ther Bio�lm-�isrupting Factorsmentioning
confidence: 94%
“…Recently, Sun et al [99] reported the antibio�lm activity of terpinen-4-ol-loaded lipid nanoparticles against C. albicans bio�lms. e compound used (10 g/mL) eradicated formed bio�lms [99].…”
Section: �Ther Bio�lm-�isrupting Factorsmentioning
confidence: 99%
“…Likewise terpinen-4-ol-loaded lipid nanoparticles were observed to eradicate C. albicans biofilms [35]. …”
Section: Antibiofilm Treatmentsmentioning
confidence: 99%